Ações coletivas como um instrumento de efetivação a direitos de propriedade intelectual - Dias, Rodrigo Mendes (2016)
This paper aims to demonstrate that class actions are legal instruments able to accomplished intellectual property rights effectiveness. In chapter one the goal is to "navigate" in the universe of intellectual property rights, highlighting; concepts, principles, Brazilian national historic of legal protection and, also, key laws related. It aims also to let the reader aware regarding the current social context, in which the main characteristic feature are the production and the consumption on a large scale. Chapter two describes how Brazilian national law´s disciplines the infringements on intellectual property rights and how such infringements cause damages that transcend the individual sphere. It also shows that the high rate of violations of intellectual property rights is reality on the streets and it is being catalyzed by the current scenario of hyper consume in such a way, either by physical commerce either by e-commerce, that collective damages are inevitable. Chapter three begins with a brief study of the principles of the collective´s rights, so, in advance, its able to shows their legal concepts and, above all, to emphasize the fact that the intellectual property rights infringements, described in the previous chapter, causes collective´s rights ineffectiveness, in such a way, that that they should be target by class actions. After all this approach path between the damage on intellectual property rights and, the correspond, ineffectiveness of collective rights, the last chapter begins with the presentation of the Brazilian collective microsystem procedural of legal protection and it is, followed by, how the class actions can be used as an appropriate legal instrument in order to protect the intellectual property rights. At last, once the assumptions intended are established, it is concluded, in such a way, that the class actions are and should be used as legal procedures aiming intellectual property right´s effectiveness